Place influences in framing and understanding climate change adaptation challenges. Issue 6 (2nd June 2016) - Lyth, Anna; Harwood, Andrew; Hobday, Alistair J.; McDonald, Jan
Abstract : The climate change literature emphasises the importance of geographical understanding for guiding adaptation, in which "place" perspectives are particularly significant. After "scale", the term "place" within the climate change adaptation literature is most often implicitly used in reference to a delineated and localised region, such as place-based risk assessment or place-based adaptation planning. Here, we use a case study of the Australian island-state of Tasmania to demonstrate the importance and particularity of place in the formation of climate change adaptation issues, problem definition and framing, and the dynamics of knowledge and praxis development across a range of research and industry sectors. We describe the significance of the place Tasmania with regard to its geographical location; its portrayal as an island place; and its cultural meaning and relations. Through a synthesis of climate change adaptation research, policy literature and engagement with researchers and stakeholders, we identify three emergent thematic place characterisations of Tasmania. We find that these characterisations have contributed directly or indirectly to the: initiation and extent of research and practical activities; the framing of adaptation issues and perspectives on potential adaptation responses in different sectors including the marine biodiversity and resources sector, small business and human health sectors. Exposing these influences is essential for focusing future adaptation activities, including research, planning, investment and practice, in Tasmania and other locations where place is a central issue.